Development of standards for prevention of folic acid deficiency in women of childbearing age, taking into account risk factors - Narmetova, M.U.; Мakhmudova А.D.; Ysupova, I.A.; Nadjimitdinova М.А. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this work was to study the complex of therapeutic and preventive measures among women of childbearing age who are preparing for pregnancy. This complex allows to prevent pathology during pregnancy and childbirth in 92% of cases, and congenital pathology associated with folic acid deficiency in 100% of cases. The results of the work allow us to predict that 71% of women with folic acid deficiency have a risk of developing pathology during pregnancy and childbirth, and the risk of developing pathology in newborns is 37.5%.